ANALISIS KEBIJAKAN PEMERINTAH PADA TEMPAT PEMROSESAN AKHIR (TPA) SAMPAH DAN DAMPAKNYA TERHADAP LINGKUNGAN DI KOTA TANJUNG PINANG - Wijaya, Agus Chandra; Frinaldi, Aldri; Rembrandt; Lanin, Dasman (Jurnal Agro Fabrica, 2024)
Waste is a global problem that is faced in all regions in Indonesia. Tanjungpinang City is located on Bintan Island, Riau Islands Province. With the 3rd highest population after Batam City and Karimun Regency, namely 1595 people/km2. Tanjungpinang City is in the Riau Islands Province, consisting of 4 sub-districts and 18 sub-districts. Ganet TPA is located in the Karang Rejo Village area, Jalan Angsana, Pinang Kencana Village, East Tanjungpinang District, Tanjungpinang City, with land status belonging to the Tanjungpinang City Government. Ganet TPA began operating in 1992 with a land area of ​​± 30,000 m², dividing the land into 4 waste storage zones. This research aims to determine the management and obstacles faced at the waste landfill in Tanjungpinang City.